COVID‐19 hypothesis: Activated protein C for therapy of virus‐induced pathologic thromboinflammation. Issue 4 (12th June 2020) - Griffin, John H.; Lyden, Patrick
Abstract: Seriously ill patients with coronavirus disease 2019 (COVID‐19) at risk for death exhibit elevated cytokine and chemokine levels and D‐dimer, and they often have comorbidities related to vascular dysfunctions. In preclinical studies, activated protein C (APC) provides negative feedback downregulation of excessive inflammation and thrombin generation, attenuates damage caused by ischemia‐reperfusion in many organs including lungs, and reduces death caused by bacterial pneumonia. APC exerts both anticoagulant activities and direct cell‐signaling activities. Preclinical studies show that its direct cell‐signaling actions mediate anti‐inflammatory and anti‐apoptotic actions, mortality reduction for pneumonia, and beneficial actions for ischemia‐reperfusion injury. The APC mutant 3K3A‐APC, which was engineered to have diminished anticoagulant activity while retaining cell‐signaling actions, was safe in phase 1 and phase 2 human trials. Because of its broad spectrum of homeostatic effects in preclinical studies, we speculate that 3K3A‐APC merits consideration for clinical trial studies in appropriately chosen, seriously ill patients with COVID‐19.